Preliminary study on the effect of Tualang honey and its silver nanoparticles on Kainic acid mediated behavioural changes in male rats - Hasim, Hidani; Zulkifli, Nurdarina Ausi; Asari, Mohd Asnizam; Muthuraju, Sangu; Visweswara Rao, Pasupuleti Visweswara; Mustapha, Muzaimi; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Penerbit Universiti Sains Malaysia, 2020)
Objectives: Excitotoxicity is a key mechanism in neurodegenerative diseases. Kainic acid (KA) is used to induce experimental excitotoxicity. Therefore, the present study investigates the effect of Tualang honey (TH) and its silver nanoparticles (THSN) on KA mediated behavioural changes in rats. Methods: Adult Sprague-Dawley male rats (n = 18) were randomised into six groups (n = 3/group): i) Control, ii) THSN, iii) KA, iv) TH + KA, v) THSN + KA and vi) Topiramate + KA groups which were pre-treated orally with distilled water, THSN (50 mg/kg body weight), Tualang honey (1.0 g/kg body weight) or Topiramate (40 mg/kg body weight), respectively, five times at 12 h intervals. Saline or KA (15 mg/kg body weight) were injected subcutaneously 30 min after last oral treatment. The latency to onset of the first generalised seizures (FGS) was recorded. Behavioural assessments such as open field test (OFT) to assess the locomotor activity and novel object recognition test (NORT) for learning and memory were performed after 24 h of KA administration. Results: On KA treatment, FGS was observed. But there is a trend of amelioration of FGS on TH+KA and THSN+KA groups when compared to KA group. Pretreatment with TH and THSN improved learning and memory as evidenced by increased recognition index in NORT when compared to untreated KA group. Interestingly, OFT results of THSN+KA group improved the locomotor activity when compared to untreated KA group. Conclusion: These findings suggest that pre-treatment with TH and THSN provides protective effect on KA mediated behavioural changes in male rats. However, further study required to understand the mechanism of action.